1999
DOI: 10.1182/blood.v94.4.1273.416k04_1273_1282
|View full text |Cite
|
Sign up to set email alerts
|

Thrombopoietin-Induced Activation of the Mitogen-Activated Protein Kinase (MAPK) Pathway in Normal Megakaryocytes: Role in Endomitosis

Abstract: Thrombopoietin (TPO) plays a critical role in megakaryocyte proliferation and differentiation. Using various cultured cell lines, several recent studies have implicated the mitogen-activated protein kinase (MAPK) pathway in megakaryocyte differentiation. In the study reported here, we examined the role played by thrombopoietin-induced MAPK activity in a cytokine-dependent cell line (BAF3/Mpl) and in primary murine megakaryocytes. In both systems, extracellular signal-regulated protein kinase (ERK) 1 and 2 MAPK… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
64
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 56 publications
(67 citation statements)
references
References 35 publications
3
64
0
Order By: Relevance
“…It has been reported that activation of the MEK–ERK (Guerriero et al ., ; Majka et al ., ; Rojnuckarin et al ., ; Severin et al ., ) and PI3K‐AKT (Geddis et al ., ; Guerriero et al ., ) signalling pathways is important for TPO‐induced megakaryocyte differentiation. We thus sought to determine whether ( R )‐TEMOSPho activates the two signalling pathways, and whether such activation is required for megakaryocytic differentiation.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…It has been reported that activation of the MEK–ERK (Guerriero et al ., ; Majka et al ., ; Rojnuckarin et al ., ; Severin et al ., ) and PI3K‐AKT (Geddis et al ., ; Guerriero et al ., ) signalling pathways is important for TPO‐induced megakaryocyte differentiation. We thus sought to determine whether ( R )‐TEMOSPho activates the two signalling pathways, and whether such activation is required for megakaryocytic differentiation.…”
Section: Resultsmentioning
confidence: 99%
“…Importantly, however, the principal signalling pathway with a critical role appears to be the PI3K–AKT pathway, as blocking this pathway led to a far more visible inhibition of megakaryocytic differentiation. In sum, at least in our in vitro system, ( R )‐TEMOSPho appears to function as TPO does with respect to intracellular signalling (Guerriero et al ., ; Majka et al ., ; Rojnuckarin et al ., ). It should be noted that the function of ( R )‐TEMOSPho is independent of TPO, although we cannot rule out the possible role of serum‐derived auxiliary factors at this point.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Since the ERK1 and ERK2 subgroup of the MAPK family members has been involved in inducing megakaryocytic maturation (Rojnuckarin et al, 1999; Guerriero et al, 2001; Miyazaki et al, 2001; Rojnuckarin et al, 2001; Jiang et al, 2002), the last group of experiments was designed to investigate whether the ERK/MAPK pathway is engaged by the interaction between TRAIL and TRAIL receptors in primary megakaryocytic cultures. For this purpose, cells were exposed to recombinant TRAIL and activation of the ERK/MAPK pathway was investigated by Western Blot performed using antibodies specific for the residues that are phosphorylated upon kinase activation.…”
Section: Resultsmentioning
confidence: 99%